Burden of HIV and tuberculosis co-infection in Montreal, Quebec - Rivest, Paul (Can J Public Health, 2014)
OBJECTIVE: Define the burden of HIV-TB co-infection and predictors of HIV screening among incident TB cases. METHODS: Analysis of surveillance data on TB incident cases reported to Montreal’s Public Health Department from 2004 to 2009. Among all reported TB cases, proportions of cases with HIV testing and HIV infection were calculated by patient characteristics. A test for linear trends was performed on the annual proportions of HIV-tested and HIV-positive cases. Adjusted odds ratios (AOR) for HIV testing at time of TB diagnosis were computed. RESULTS: A total of 778 incident TB cases were included in the analysis. HIV testing was reported for 50.8% (n=395) of cases. The proportion of HIVtested cases increased significantly from 43% in 2004 to 70% in 2009. HIV-TB co-infection was found in 9.3% of patients with reported HIV status or in 4.2% of the overall cohort. HIV prevalence was high in men, individuals aged 40-59, those originating from Sub-Saharan Africa and the Caribbean, and the homeless. Multivariate analysis revealed that HIV testing at time of TB diagnosis was performed mainly for subjects born in the Caribbean, Central or South America, or Sub-Saharan Africa, those with pulmonary disease, and injection drug users. CONCLUSIONS: Although reporting of HIV testing among incident TB patients increased, targeted HIV testing still occurs. HIV prevalence in TB cases remained stable during the study period; however, it may be underestimated due to missed opportunities for HIV testing and under-reporting.